Role of Glutathione in Cardiovascular System Physiology - Asker, Mohammed H.; Emad, Noor Al-Mustafa; Al-Zuaini, Hashim H. (Medical Science Journal for Advance Research, 2024)
Background: The three-amino acid compound glutathione contains cysteine and is a tripeptide of cysteine, glutamate, and glycine and is the major antioxidant defense mechanism within eukaryotic cells. Participating in the removal of reactive oxygen species, it contributes in maintaining redox equilibrium and cellular homeostasis and is of particular importance in cardiovascular system. Purpose: This review aims at reviewing the literature on the biosynthesis and metabolism of glutathione and the ways that its actions is regulated for purposes of understanding its roles in cardiovascular physiology. The most critical aspect of the glutathione actions contributes to the reduction of oxidative stress, which is vital for maintaining the endothelium and vessel walls. That will help to eliminate toxic metabolites, is involved in mitochondrial processes, and improve the cardiovascular system’s resistance to ischemia/reperfusion damage. As shown by various researches and studies, heart failure and hypertension, and other cardiovascular diseases are associated with low glutathione levels or disruption of glutathione homeostasis, which only establishes the significance of maintaining adequate glutathione levels. This review makes a plea for the utilization of glutathione to reduce and combat oxidative stress, enhance endothelium stability, and protect the myocardium. Thus, the understanding of the pathways involved in the regulation of the cardiovascular system by glutathione can provide the basis for the design of new and effective preventive and therapeutic interventions for CVDs with a focus on aging and oxidative stress-related diseases. Additional studies are needed to collectively examine the potential treatments of glutathione which seems to improve cardiovascular functioning and hence heart health. Conclusion: This research has shown that glutathione is highly effective in the health of the cardiovascular system due to its antioxidant properties, detoxification mechanism, and control of endothelium. This review is aimed at the use of glutathione supplementation in the treatment of oxidative stress and decrease in cardiovascular risk. Understanding the roles of glutathione and the roles it plays in cardiovascular diseases gives new opportunities for the prevention and treatment of cardiovascular diseases, especially the ones that are associated with aging and oxidative stress.